Assessment of two‐pool multiplex long‐amplicon nanopore sequencing of SARS‐CoV‐2. Issue 1 (23rd September 2021) - Liu, Hongjie; Li, Jinhui; Lin, Yanfeng; Bo, Xiaochen; Song, Hongbin; Li, Kuibiao; Li, Peng; Ni, Ming
Abstract: Genomic surveillance of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) plays an important role in COVID‐19 pandemic control and elimination efforts, especially by elucidating its global transmission network and illustrating its viral evolution. The deployment of multiplex PCR assays that target SARS‐CoV‐2 followed by either massively parallel or nanopore sequencing is a widely‐used strategy to obtain genome sequences from primary samples. However, multiplex PCR‐based sequencing carries an inherent bias of sequencing depth among different amplicons, which may cause uneven coverage. Here we developed a two‐pool, long‐amplicon 36‐plex PCR primer panel with 1000‐bp amplicon lengths for full‐genome sequencing of SARS‐CoV‐2. We validated the panel by assessing nasopharyngeal swab samples with a <30 quantitative reverse transcription PCR cycle threshold value and found that ≥90% of viral genomes could be covered with high sequencing depths (≥20% mean depth). In comparison, the widely‐used ARTIC panel yielded 79%–88% high‐depth genome regions. We estimated that 5 Mbp nanopore sequencing data may ensure a >95% viral genome coverage with a ≥10‐fold depth and may generate reliable genomes at consensus sequence levels. Nanopore sequencing yielded false‐positive variations with frequencies of supporting reads <0.8, and the sequencing errors mostly occurred on the 5′ or 3′ ends of reads. Thus, nanopore sequencing could not elucidate intra‐host viral diversity.